Strengths and Challenges of Implementing Physiotherapy in an HIV Community-Based Care Setting: A Qualitative Study of Perspectives of People Living with HIV and Healthcare Providers. (26th March 2021) - Vader, Kyle; Carusone, Soo Chan; Aubry, Rachel; Ahluwalia, Puja; Murray, Carolann; Baxter, Larry; Robinson, Gregory; Ibáñez-Carrasco, Francisco; Stewart, Ann; Solomon, Patricia; O'Brien, Kelly K.
The needs of people living with HIV (PLWH) who have access to antiretroviral therapy have shifted from hospital to community care; however, little is known about physiotherapy within HIV community-based care. Our aim was to understand strengths and challenges of implementing physiotherapy within an interprofessional HIV day health program in Toronto, Ontario, Canada. We conducted a qualitative descriptive study using semi-structured interviews. Data were analyzed using inductive content analysis. Fifteen PLWH and 5 healthcare providers participated. Strengths included improved access to physiotherapy and fulfilling an unmet need for rehabilitation; a tailored approach to physiotherapy; co-location improved communication, coordination, and engagement in care; and improved health outcomes for PLWH (i.e. function, psychosocial outcomes, and quality of life). Challenges related to managing expectations; variable attendance at visits; and managing complex and diverse needs of PLWH. Results may be transferable to other community-based care settings that provide care for PLWH and complex multi-morbidity.